Proceedings of the 2012 ACM Workshop on Privacy in the Electronic Society 2012
DOI: 10.1145/2381966.2381983
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sharing preferences and behavior for mHealth devices

Abstract: If people are not in control of the collection and sharing of their personal health information collected using mobile health (mHealth) devices and applications, privacy concerns could limit their willingness to use and reduce potential benefits provided via mHealth. We investigated users' willingness to share their personal information, collected using mHealth sensing devices, with their family, friends, third parties, and the public. Previous work employed hypothetical scenarios, surveys and interviews to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 15 publications
4
49
0
Order By: Relevance
“…Our participants sought to protect their family and friends through the hiding of negative moods and health problems, which supports the work of Prasad et al, [43]. While they may hide health information from some individuals, they are open to others who might help them manage better.…”
Section: Discussionsupporting
confidence: 63%
“…Our participants sought to protect their family and friends through the hiding of negative moods and health problems, which supports the work of Prasad et al, [43]. While they may hide health information from some individuals, they are open to others who might help them manage better.…”
Section: Discussionsupporting
confidence: 63%
“…Similar to our experiment, the study by Prasad et al [25] investigates information sharing behaviour in mHealth, when users have options to share with friends, family, third parties and the public. However, we are interested in investigating the sharing behaviour in a purpose-driven mHealth scenario, i.e.…”
Section: Privacy and Information Sharingmentioning
confidence: 85%
“…So far, most investigations in this research area are based on surveys and user interviews. To the best of our knowledge, an experiment by Prasad et al [25] is the first study that collects data and investigates privacy concern related to data sharing with real user interactions. Such studies are resource intensive, difficult to execute and reproduce, and can take a considerable amount of time.…”
Section: Privacy and Information Sharingmentioning
confidence: 99%
“…the location of their health information and which parties and/or organisations have access to it. Furthermore, a study by Prasad et al [66], also from 2012, proposes that a highly granular control is required in sharing of health information. This means detailed and perhaps subtle application of access control rules to health data, i.e.…”
Section: Security and Privacymentioning
confidence: 99%
“…According to [60] and [66], the studies by Adams et al [73], Caine et al [74], and Lim et al [75] have suggested that patients should have full control of who can access their data. However, most of the studies in this area are applied to EHR / PHR, to allow patients to maintain and manage their own medical records and share them under a patient's control.…”
Section: Security and Privacymentioning
confidence: 99%